Zero-dimensional hybrid indium halide materials, their preparation methods and applications

The zero-dimensional hybrid indium-based halide [DADPA] InX6·H2O prepared by low-temperature solution synthesis method solves the problems of low light yield and complex preparation of existing three-dimensional lead halide perovskite nanocrystals, and achieves high-light quantum yield and excellent X-ray scintillation performance.

CN116425640BActive Publication Date: 2025-02-18JINING UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310228074.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-10
Publication Date
2025-02-18
Estimated Expiration
2043-03-10

AI Technical Summary

Technical Problem

The existing three-dimensional lead halide perovskite nanocrystals have low light yields under X-ray excitation, and the preparation process is complex, high cost, large energy consumption, and affect environmental protection.

Method used

By a simple low-temperature solution synthesis method, zero-dimensional hybrid indium-based halide [DADPA] InX6·H2O was prepared, and DADPA and InX3 were used as starting materials, and heated at 60-85°C for at least 5 days to obtain a yellow-orange luminescent High-quality luminescent body.

Benefits of technology

The high-light quantum yield is achieved close to 100%, and the Sb3+ doped [DADPA] InCl6·H2O shows excellent X-ray scintillation performance, the photo yield can reach 51,875 photons/MeV, the detection limit is 98.3nGyair s-1, with Strong radiative luminescence stability and ultra-high spatial resolution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention discloses a zero-dimensional hybrid indium-based halide material and a preparation method and application thereof, belonging to the technical field. The technical scheme is as follows: the molecular formula of the zero-dimensional hybrid indium-based halide material is [DADPA]InX6·H2O, wherein DADPA is 3,3'-diaminodipropylamine, and X is Br or Cl. The present invention focuses on exploring efficient 0D hybrid indium halide materials with excellent scintillation performance. Through a simple low-temperature solution synthesis method, two 0D hybrid indium halides [DADPA]InX6·H2O with novel structures and photoquantum yields close to 100% are prepared as high-quality luminophores with yellow-orange luminescence.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of luminescent materials, and in particular to a zero-dimensional hybrid indium-based halide material and a preparation method and application thereof. Background Art

[0002] As an important optoelectronic functional material, scintillator can absorb X-rays and convert high-energy radiation into ultraviolet-visible-infrared light, and has many advantages such as fast response speed and large absorption cross section. In the past few decades, including CsI:Tl, LaBr3:Ce, CdWO4, Bi4Ge3O 12 Many inorganic scintillating materials, including , have been widely used in commercial X-ray detection. However, these traditional scintillating materials often require complex high-temperature synthesis methods to prepare, and are costly and energy-intensive, which is neither environmentally friendly nor convenient. Therefore, in order to improve this adverse effect, three-dimensional lead halide perovskite nanocrystals (PNCs) synthesized in low-temperature solutions have gradually become a new generation of X-ray scintillator candidate materials due to their simple preparation process, high photon quantum yield, inherent atomic number and absorption coefficient, and adjustable emission wavelength covering the entire visible light range. However, the only drawback is that due to the low exciton binding energy and inevitable self-absorption effect, the light yield of three-dimensional PNCs (21000 photons / MeV) lags far behind typical commercial scintillators such as CsI:Tl (54000 photons / MeV) and NaI:Tl (45000 photons / MeV). Therefore, it is difficult but of great significance to explore new perovskite materials as environmentally friendly, efficient and stable X-ray scintillators.

[0003] In recent years, zero-dimensional (0D) metal halides have been considered as one of the promising candidate materials for three-dimensional PNCs due to their various advantages, such as structural diversity, adjustable luminescence properties, ultra-high quantum yield and sufficient luminescence stability. The difference is that compared with the inflexible three-dimensional network and band-edge emission of PNCs, zero-dimensional metal halides have multifunctional organic species and a large number of inorganic metal ions (Cu + 、Zn 2+ , Mn 2+ 、In 3+ , Sb 3+etc.), giving it more opportunities to coordinate structure and luminescence properties. Since inorganic units are in a discrete state in the lattice for a long time or are periodically embedded in an insulating organic matrix by clusters, zero-dimensional hybrid halides have a strong quantum confinement effect, resulting in their ultra-high exciton binding energy and luminescence efficiency. At the same time, the softness and deformability of the lattice make the zero-dimensional structure have a strong electron-phonon coupling effect in the excited state, thus forming a self-trapped exciton broadband light emission related to the Stokes shift. Therefore, zero-dimensional hybrid metal halides have become the most promising X-ray scintillators due to the synergistic effect of high light quantum yield and low absorption characteristics.

[0004] So far, many zero-dimensional lead-free halides based on metal ions such as copper (I), silver (I), manganese (II), and tin (II) have been considered as new generation scintillating materials. 2- Tetrahedron (C 38 H 34 P2)MnBr4,(C4H 12 0D hybrid manganese halides such as (N)MnCl3 and (TPP)2MnBr4 show strong green radiation luminescence performance under X-ray excitation, and their light yield can reach 80,000 photons / MeV, and the spatial resolution is also as high as 15 lp / mm or more. 20 0D hybrid copper halides such as (N)2Cu2Br4, (AEP)2Cu2I6·2I·2H2O, and (DIET)3Cu3X3 also have rich radiative luminescence properties in the entire visible light range, with a maximum light yield of 91300 photons / MeV and a spatial resolution of 15.7 lp / mm. In addition, some tin (II)-based 0D hybrid halides, such as (Bmpip)2SnBr4, have also been reported as a new generation of scintillating materials. These remarkable X-ray scintillation properties strongly demonstrate the superiority of 0D hybrid metal halides over 3D PNCs, but Mn 2+ Hygroscopicity of base halides and Cu + and Sn 2+ Unfavorable factors such as the low oxidation resistance of halides need to be further resolved before commercial use. Summary of the invention

[0005] The technical problem to be solved by the present invention is: to overcome the shortcomings of the prior art, to provide a zero-dimensional hybrid indium-based halide material and a preparation method and application thereof, to focus on exploring efficient 0D hybrid indium halide materials with excellent scintillation performance, and to prepare two 0D hybrid indium halides [DADPA]InX6·H2O with novel structures and a photoquantum yield close to 100% as high-quality luminophores emitting yellow-orange light through a simple low-temperature solution synthesis method.

[0006] The technical solution of the present invention is:

[0007] In a first aspect, the present invention provides a zero-dimensional hybrid indium-based halide material, wherein the molecular formula of the zero-dimensional hybrid indium-based halide material is [DADPA]InX6·H2O, wherein DADPA is 3,3'-diaminodipropylamine, and X is Br or Cl; when X is Br, the crystal system space group is P-1 , unit cell parameters a =7.8936(3)Å, b =11.0840(5)Å, c =12.1633(5)Å, α=94.554(2)º, β= 108.689(2)º,γ=109.0060(10)º, Z =2, the unit cell volume is V =932.854Å 3 ; When X is Cl, the crystal system space group is P-1 , unit cell parameters a =7.54750(10) Å, b =10.68050(10) Å, c =11.8682(2) Å, α=94.6940(10)º, β= 107.997(2)º,γ=109.4970(10)º, Z =2, the unit cell volume is V =839.274 Å 3 .

[0008] Preferably, when X is Cl, the zero-dimensional hybrid indium-based halide material is doped with antimony, and the resulting material has the molecular formula [DADPA]In 0.83 Sb 0.17 Cl6∙H2O.

[0009] In a second aspect, the present invention provides a method for preparing the above-mentioned zero-dimensional hybrid indium-based halide material, wherein InX3 and 3,3'-diaminodipropylamine are added to a mixed solution, and the solution is continuously heated and stirred to dissolve; the resulting solution is transferred and sealed in a reaction container, and then heated at 60-85°C for at least 5 days, and cooled to room temperature.

[0010] Preferably, the molar ratio of InX3 to 3,3'-diaminodipropylamine is 1:(1-3).

[0011] Preferably, the mixture is heated to 60-80° C. and stirred to dissolve InX3 and 3,3′-diaminodipropylamine.

[0012] Preferably, when X is Br, the mixed solution is HBr and acetonitrile; when X is Cl, the mixed solution is HCl, ethanol and acetonitrile.

[0013] Preferably, the volume ratio of HBr to acetonitrile is 1:(3-5); the volume ratio of HCl, ethanol and acetonitrile is 1:(2-3):(1-4).

[0014] Preferably, when X is Cl, antimony element is doped into the zero-dimensional hybrid indium-based halide material, and the specific operation is as follows: InCl3, SbCl3 and 3,3'-diaminodipropylamine are added to the mixed solution, and the solution is continuously heated and stirred to dissolve; the resulting solution is transferred and sealed in a reaction container, and then heated at 60-85°C for at least 5 days, and cooled to room temperature.

[0015] Preferably, the molar ratio of InCl3, SbCl3 and 3,3'-diaminodipropylamine is (1-2): (1-2):1.

[0016] In a third aspect, the present invention also provides an application of the above zero-dimensional hybrid indium-based halide material, wherein the zero-dimensional hybrid indium-based halide material is applied to the fields of white light emitting diodes, X-ray scintillation and fluorescent probes.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The present invention focuses on exploring efficient 0D hybrid indium halide materials with excellent scintillation performance. Through a simple low-temperature solution synthesis method, two 0D hybrid indium halides [DADPA]InX6·H2O with novel structures and photon quantum yields close to 100% are prepared as high-quality luminophores for yellow-orange luminescence. In addition, Sb 3+ The doped [DADPA]InCl6·H2O exhibits excellent X-ray scintillation performance, with a light yield of up to 51875 photons / MeV and a detection limit of 98.3nGyair s -1 , and exhibits strong radioluminescence stability. At the same time, the present invention further proves its ultra-high spatial resolution (25.15 lp / mm) and extremely short afterglow time (2.75ms) through X-ray imaging engineering. This is the first hybrid indium halide-based scintillator material. The discovery of this material has greatly broadened the application field of lead-free metal halides and opened a new window for exploring ideal X-ray scintillator materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1The structures and photoluminescence properties of the compounds prepared in Examples 1 and 2 of the present invention, wherein Figure (a) is the crystal structure observed along the a-axis; Figure (b) is the experimental and simulated PXRD patterns; Figure (c) is the CIE coordinates and a photograph of the bulk crystal under ultraviolet light irradiation; Figures (d) and (e) are the PL excitation and emission spectra of [DADPA]InBr6·H2O and [DADPA]InCl6-H2O, respectively; Figures (f) and (g) are the three-dimensional continuous PL excitation and emission diagrams of [DADPA]InBr6·H2O and [DADPA]InCl6-H2O, respectively; Figures (h) and (i) are the time-resolved PL decay curves of [DADPA]InBr6·H2O and [DADPA]InCl6-H2O, respectively.

[0020] Figure 2 The SEM photograph (a), EDS result (b) and elemental spectrum (c) of the compound crystal prepared in Example 1 of the present invention.

[0021] Figure 3 The SEM photograph (a), EDS result (b) and elemental spectrum (c) of the compound crystal prepared in Example 2 of the present invention.

[0022] Figure 4 The emission wavelength-dependent excitation spectrum (a) and the excitation wavelength-dependent emission spectrum (b) of the compound prepared in Example 1 of the present invention are shown.

[0023] Figure 5 The emission wavelength-dependent excitation spectrum (a) and the excitation wavelength-dependent emission spectrum (b) of the compound prepared in Example 2 of the present invention are shown.

[0024] Figure 6 The emission spectra of the bulk crystals and nanocrystals of the compound prepared in Example 1 of the present invention (a) and the emission spectra of the bulk crystals and nanocrystals of the compound prepared in Example 2 (b).

[0025] Figure 7 The power-dependent emission spectrum (a) of the compound prepared in Example 1 of the present invention and the power-dependent emission spectrum (b) of the compound prepared in Example 2.

[0026] Figure 8Figures (a) and (e) are the UV-visible absorption spectra of the compounds prepared in Examples 2 and 3, respectively; Figures (f) and (g) are the calculated band structures of the compounds prepared in Examples 2 and 3, respectively; Figures (h) and (i) are the total state density and partial state density of the compounds prepared in Examples 2 and 3, respectively; Figure (j) is the PL emission spectrum of the compound prepared in Example 3 as a function of temperature; Figure (k) is a graph showing the relationship between the experimental and fitted emission intensity and the reciprocal temperature of the compound prepared in Example 3, as well as the FWHM fitted according to Formula II.

[0027] Fig. 9 The photoluminescence quantum yields of the compounds prepared in Examples 1-3 of the present invention, wherein Figures (a), (b) and (c) correspond to Example 1, Example 2 and Example 3, respectively.

[0028] Fig.10 The powder X-ray diffraction pattern of the compound prepared in Example 3 of the present invention.

[0029] Fig.11 The SEM image (a), EDS result (b) and elemental spectrum (c) of the compound prepared in Example 3 of the present invention.

[0030] Fig.12 The three-dimensional continuous PL excitation and emission diagram (a), emission wavelength-related excitation spectrum (b) and excitation-related emission spectrum (c) of the compound prepared in Example 3 of the present invention.

[0031] Fig.13 PL emission spectra (a) and excitation power-dependent emission spectra (b) of bulk crystals and nanocrystals of the compound prepared in Example 3 of the present invention.

[0032] Fig.14 The contribution of the temperature-dependent PL energy evolution, thermal expansion and electron-phonon interaction of the compound prepared in Example 3 of the present invention.

[0033] Fig.15 This is the Raman spectrum of the compound prepared in Example 3 of the present invention.

[0034] Fig.16 Experimental PXRD pattern (a) and PL emission spectrum (b) of the compound prepared in Example 3 of the present invention in humid air.

[0035] Fig.17The characteristics of the white light LED manufactured by the compound prepared in Example 3 of the present invention, wherein Figure (a) is the EL emission spectrum under a driving current of 20mA, and the inset in Figure (a) is a photo of the white light LED manufactured before and after the power supply is switched on; Figure (b) is the CIE chromaticity coordinates; and Figure (c) is the PL emission spectrum related to the driving current.

[0036] Fig.18 The properties of the compound prepared in Example 4 of the present invention as a fluorescent probe: Figure (a) is a luminescent photograph of the nanodispersion after adding various organic solvents; Figure (b) is the PL emission spectrum of the nanodispersion after adding various organic solvents; Figure (c) is the normalized emission intensity of the nanodispersion after adding various organic solvents; Figure (d) is a photograph of the nanodispersion under ultraviolet irradiation during continuous quenching-recovery cycles and the relationship between the PL emission intensity in C6H5NO2 and the cycle number; Figure (f) is a photograph of the nanodispersion after adding different concentrations of C6H5NO2 (the concentration calculated by volume is 1×10 -7 Up to 1×10 -2 ), PL emission spectrum of the nanodispersion; Figure (g) is the linear fitting of the emission intensity ratio and C6H5NO2 concentration.

[0037] Fig.19 This is a SEM photo image of the nanoparticles prepared in Example 4 of the present invention.

[0038] Fig. 20 PL emission spectra of the nanoparticles prepared in Example 4 of the present invention in various organic solvents.

[0039] Fig.21 Figures 2 and 3 show the PL emission spectra of the nanoparticles prepared in Example 4 of the present invention for nitrobenzene in various organic solvents with a concentration of 0% and 1%, wherein the organic solvents corresponding to Figures (a) to (i) are benzene, xylene, ethylbenzene, vinylbenzene, methoxybenzene, fluorobenzene, chlorobenzene, bromobenzene and iodobenzene, respectively.

[0040] Fig. 22 The following are the powder diffraction patterns of the nanoparticles prepared in Example 4 of the present invention in various organic solvents.

[0041] Fig.23 The relationship between the absorption coefficient of the compounds prepared in Examples 1-3 of the present invention and commercial Ce:LuAG and the photon energy from 1 KeV to 1000 KeV.

[0042] Fig.24The radioluminescence properties related to the compound prepared in Example 3 of the present invention are shown, wherein Figure (a) is the RL spectra of Examples 1-3 and Ce:LuAG; Figure (b) is a comparison of the light yields of Example 3 and some commercial scintillators; Figure (c) is the RL emission spectrum of Example 3 measured at different X-ray dose rates; Figure (d) is the linear relationship between the RL intensity and X-ray dose rate of Example 3; and Figure (e) is the RL stability of Example 3 under continuous X-ray irradiation.

[0043] Fig.25 Schematic diagram of the compound prepared in Example 3 of the present invention applied to a digital X-ray optical imaging system (a); photography under sunlight and X-ray images of an electronic power box and a packaged fuse (b); MTF curve of the manufactured scintillator screen (c); comparison of the spatial resolution of the scintillator screen and other halide scintillators (d); afterglow curve caused by X-rays (e).

[0044] Fig.26 The figure is the powder X-ray diffraction pattern of the compound prepared in Comparative Example 1 of the present invention.

[0045] Fig. 27 The excitation spectrum and emission spectrum of the compound prepared in Comparative Example 1 of the present invention at 300K.

[0046] Fig.28 It is the quantum yield of the compound prepared in Comparative Example 1 of the present invention at 300K.

[0047] Fig.29 The figure is the powder X-ray diffraction pattern of the compound prepared in Comparative Example 2 of the present invention.

[0048] Fig.30 The excitation spectrum and emission spectrum of the compound prepared in Comparative Example 2 of the present invention at 300K.

[0049] Fig.31 It is the quantum yield of the compound prepared in Comparative Example 2 of the present invention at 300K. DETAILED DESCRIPTION

[0050] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention. The experimental methods described in the following embodiments are conventional methods unless otherwise specified; if no specific techniques or conditions are specified in the embodiments, they are carried out according to the techniques or conditions described in the literature in the field or according to the product instructions; the reagents and materials, unless otherwise specified, can be obtained from commercial channels.

[0051] 1. Materials used in the following examples

[0052] The raw materials used in the embodiments of the present invention are all provided by Aladdin Reagent Company: indium trichloride tetrahydrate (purity 99.9%), indium tribromide (purity 99.9%), antimony trichloride (purity 99.9%), 3,3'-diaminodipropylamine (99%), ethanol, hydrobromic acid, hydrochloric acid, acetonitrile; the reaction container is a 25mL glass bottle that can withstand temperatures below 120°C.

[0053] 2. Instruments and testing methods

[0054] The electric heating blast drying oven was provided by Shanghai Yiheng Scientific Instrument Co., Ltd., model DHG-9240(A).

[0055] The crystal structure was determined by single crystal X-ray diffractometer (SMART APEXII, Bruker, Germany).

[0056] The powder diffraction was measured by X-ray powder diffractometer (Bruker D8 ADVANCE), and the UV-visible absorption spectrum was measured by UV-visible spectrophotometer (PE Lambda 900).

[0057] PL spectroscopy was performed on an Edinburgh FLS980 fluorescence spectrometer.

[0058] The photoluminescence quantum yield was achieved by adding an integrating sphere to the FLS980 fluorescence spectrometer.

[0059] The thermal stability test was performed by thermogravimetric analysis (TGA) on a Mettler TGA / SDTA 851 thermal analyzer in the temperature range of 30-800°C under the constant protection of N2 atmosphere flow.

[0060] Example 1 Preparation of [DADPA]InBr6·H2O

[0061] 1) Add InBr3 (1 mmol, 0.354 g) and 3,3'-diaminodipropylamine (DADPA, 0.3 mL) to a mixed solution of HBr (1.5 mL) and acetonitrile (4 mL), and continue heating and stirring to 60 °C to dissolve;

[0062] 2) The solution was transferred and sealed in a 15 mL glass bottle, then heated at a constant temperature of 60 °C for 5 days and cooled to room temperature at a cooling rate of 5 °C / min to obtain [DADPA]InBr6·H2O crystals.

[0063] The molecular formula of the crystal prepared in the final embodiment 1 is [DADPA]InBr6·H2O, and the crystal system space group is P-1 , unit cell parameters a =7.8936(3)Å,b =11.0840(5)Å, c =12.1633(5)Å, α=94.554(2)º, β= 108.689(2)º,γ=109.0060(10)º, Z =2, the unit cell volume is V =932.854Å 3 .

[0064] Example 2 Preparation of [DADPA]InCl6·H2O

[0065] 1) Add InCl3·4H2O (0.5 mmol, 0.1466 g) and 3,3'-diaminodipropylamine (DADPA, 0.175 mL) to a mixed solution of HCl (1 mL), ethanol (1 mL) and acetonitrile (4 mL), and continue heating and stirring to 80 °C to dissolve;

[0066] 2) The solution was transferred and sealed in a 25 mL glass bottle, then heated at a constant temperature of 80°C for 5 days and cooled to room temperature at a cooling rate of 5°C / min. [DADPA]InCl6·H2O crystals were obtained.

[0067] The molecular formula of the crystal prepared in Example 2 is [DADPA]InCl6·H2O, and the crystal system space group is P-1 , unit cell parameters a =7.54750(10) Å, b =10.68050(10) Å, c =11.8682(2) Å, α=94.6940(10)º, β= 107.997(2)º,γ=109.4970(10)º, Z =2, the unit cell volume is V =839.274 Å 3 .

[0068] The present invention successfully synthesized a single crystal of [DADPA]InX6·H2O using DADPA and InX3 as starting materials by a simple low-temperature solution method. The single crystal X-ray diffraction pattern shows that the crystal structure of [DADPA]InX6·H2O is in the triclinic space group P- 1 in crystallization. Figure 1 a shows the crystal structure of [DADPA]InX6·H2O, which contains two crystallographically independent In sites and six X - ions and a [DADPA] 3+ Cation. Two In 3+ The ions are all six X -Ion coordination is [InX6] 3- The In-X bond distances for octahedral, bromine and chlorine are 2.6410-2.6979 Å and 2.4888-2.5369 Å, respectively. All [InX6] 3- The octahedron is filled with a large amount of [DADPA] 3+ The cations are divided and surrounded, thus forming a zero-dimensional hybrid structure; at the same time, the hybrid structure contains abundant weak hydrogen bonds and the guest H2O molecules in the structure are located in free space. Figure 1 As shown in b, the powder X-ray diffraction (PXRD) pattern of the sample is consistent with the simulation data of the single crystal structure, indicating that it has a high purity. Figure 2 As shown in Figs. ab and 3a-b, semi-quantitative elemental analysis based on energy dispersive spectroscopy (EDS) confirmed that the molar ratios of In:Br and In:Cl were approximately 1:6.2 and 1:6.1, which are close to the results of single crystals. Figure 2 As shown in Figures 3c and 3c, the scanning electron microscope (SEM) coupled elemental mapping of the crystal surface shows that the distribution of C, N, In and Br or Cl is uniform, which also proves that the prepared single crystal has high purity.

[0069] like Figure 1 As shown in Figure c, under the excitation of ultraviolet light, the transparent bulk crystals of [DADPA]InBr6·H2O and [DADPA]InCl6·H2O respectively show bright orange and yellow light. The present invention then studies its luminescence properties through detailed spectroscopy such as steady-state and time-resolved fluorescence spectroscopy. Figure 1 As shown in Figure d, under the excitation of 363 nm UV light, [DADPA]InBr6·H2O shows a broadband spectral emission centered at 575 nm, with a large Stokes shift of 212 nm (1.26 eV) and a maximum half-peak width of 130 nm. Figure 1 As shown in Figure e, under 358 nm ultraviolet excitation, the emission peak of [DADPA]InCl6·H2O exhibits a Gaussian shape with a peak value of 554 nm and a Stokes shift of 196 nm (1.22 eV). Figure 1 As shown in Fig. c, the calculated CIE coordinates are (0.56, 0.36) and (0.40, 0.51), which are also located in the orange and yellow regions of [DADPA]InBr6·H2O and [DADPA]InCl6·H2O, respectively. In order to confirm the source of these broadband light emissions, the present invention measured the wavelength-dependent excitation and emission spectra at room temperature. Figure 4-5 As shown in Figure 1, under different excitation wavelengths, all emission spectrum curves are almost the same. Figure 1As shown in Fig. 1f and 1g, only one emission center is observed in the three-dimensional continuous PL excitation and emission diagram of [DADPA]InX6·H2O, which indicates that the broadband light emission should come from the relaxation of the same excited state. In order to reveal the dynamic change process of the emission, the present invention records its resolved spectrum at the corresponding time. Figure 1 As shown in h and 1i, at 300K, according to the double exponential fitting, the luminescence decay curves of [DADPA]InBr6·H2O and [DADPA]InCl6·H2O are 3.527 μ s and 4.172 μ At 80K, due to the increase in radiation probability, the lifetime is extended to 4.042 μ s and 5.825 μ s. In addition, the difference between the emission spectra of bulk crystals and tiny particles is negligible, which excludes the possibility of broadband light emission caused by surface defects. Figure 6-7 As shown, the linear relationship between emission intensity and excitation power density further confirms this conclusion.

[0070] like Figure 8 a and Fig. 9 As shown in a-9b, the photon quantum yields of [DADPA]InBr6·H2O and [DADPA]InCl6·H2O are 27.39% and 41.27%, respectively. The latter is superior to the previously reported (PMA)3InBr6 (35%), Cs2InBr5·H2O (33%), (C4H 14 N2)2In2Br 10 (3%), [DAPEDA]InCl6·Cl·H2O (40%) and (DPA)3InCl6(34%) and other zero-dimensional indium halide materials.

[0071] In order to further optimize its photon yield, the present invention firstly considers the Sb-based 3+ The halides have ultra-high photon yields and In 3+ / Sb 3+ Ionic radii (In 3+ :0.91 Å and Sb 3+ :0.90 Å), so the present invention further conducted a reasonable Sb 3+ Doping strategy, the specific operations are as follows:

[0072] Example 3 [DADPA]In 0.83 Sb 0.17 Preparation of Cl6∙H2O

[0073] 1) Add InCl3·4H2O (0.5mmol, 0.1466g), SbCl3 (1mmol, 0.2290g) and 3,3'-diaminodipropylamine (DADPA, 0.175mL) to a mixed solution of HCl (1mL), ethanol (1mL) and acetonitrile (4mL), and continue heating and stirring to 70℃ to dissolve;

[0074] 2) The solution was transferred and sealed in a 25 mL glass bottle, then heated at a constant temperature of 80 °C for 5 days and cooled to room temperature at a cooling rate of 5 °C / min to obtain [DADPA]In 0.83 Sb 0.17 Colorless crystals of Cl6∙H2O with a yield of 76%.

[0075] like Fig.10 As shown, Sb 3+ The powder diffraction pattern of the phase matches that of [DADPA]InCl6·H2O, indicating that their crystal structures are identical. Fig.11 As shown in the EDS, the coexistence of In and Sb further verifies that Sb 3+ The doping was successful, and the elemental map also revealed the uniform distribution of In and Sb on the bulk crystal surface. The exact doping concentration of Sb was confirmed to be 0.17% by inductively coupled plasma optical emission spectroscopy (ICP-OES). The doped phase can be expressed as [DADPA]In 0.73 Sb 0.17 Cl6·H2O (as shown in Table 1).

[0076] Table 1

[0077]

[0078] In addition, if Figure 8 As shown in b, [DADPA]In 0.73 Sb 0.17 Cl6·H2O shows almost the same broadband yellow emission as the undoped phase, with the maximum peak at 552nm. It is worth noting that Figure 8 c and 9c, [DADPA]In 0.73 Sb 0.17 The light quantum yield of Cl6·H2O is 91.7%, which is much higher than that of the original undoped phase, and the luminescence lifetime is also extended to 6.252 μ s (300K) and 8.532 μ s (80K), which indicates that Sb 3+ The doping of Sb can effectively promote the radiative recombination rate. 3+ The basic mechanism of the doping strategy, the present invention is to [DADPA]InCl6·H2O and [DADPA]In0.73 Sb 0.17 Cl6·H2O was compared with experimental tests and theoretical calculations. Figure 8 d and 8e, [DADPA]InCl6·H2O and [DADPA]In 0.73 Sb 0.17 The UV-visible absorption spectrum of Cl6·H2O shows a similar steep absorption edge with weak shoulders below the cutoff wavelength, which are derived from In 3+ or Sb 3+ ions. The difference is that Sb 3+ The incorporation of leads to a slight decrease in the band gap from 3.51eV to 3.32eV. The electronic band structure can explain the enhancement of the photon quantum yield. Figure 8 As shown in Figures 8f and 8g, due to the limitations of the CASTEP software, the band structure directly gives a band gap of 3.21eV and 3.01eV, which is slightly smaller than the absorption spectrum. For these two zero-dimensional halides, the valence band and conduction band near the Fermi level are extremely flat, indicating that the electrons are highly localized and the effective mass of the carriers is large, which is conducive to the formation of bound excitons. Figure 8 h and 8i, the total and partial state densities show that the valence band maximum (VBM) and conduction band minimum (CBM) are mainly caused by In / Sb-5 s 5 p and Cl-3 p state contribution, while the contribution of the organic component is negligible, indicating that the optical properties of zero-dimensional hybrid halides are mostly due to the anion [In / SbCl6] 3- Compared with [DADPA]InCl6·H2O, Sb 3+ Dopants mainly cause the valence band to shift upward and Sb-5 p The narrow gap inner band of the state, while the conduction band remains unchanged. Therefore, the doped Sb 3+ Inducing the formation of an impure band gap, thereby increasing the electron density in the valence band, promoting more carriers to enter the conduction band, and ultimately improving the emission efficiency.

[0079] like Figure 12-13 As shown, the present invention further verifies [DADPA]In by three-dimensional continuous PL images and emission spectra related to excitation power density. 0.73 Sb 0.17 Cl6·H2O has a dominant emission center. In order to further explore the luminescence mechanism of broadband light emission, the present invention further collected [DADPA]In 0.73 Sb 0.17 The emission spectrum of Cl6·H2O changes with temperature from 80 K to 300 K. Figure 8As shown in Fig. 1, with the increase of temperature, the maximum emission wavelength gradually redshifts from 570 nm to 552 nm. Based on the theoretical fitting of the emission energy, it is verified that the blue shift is mainly due to the contribution of electron-phonon coupling (e.g. Fig.14 At the same time, there is no spectrum splitting phenomenon in the temperature range of 80K to 300K, which verifies that the emission does not belong to multiple excited states being excited simultaneously but a single emission center. With the enhancement of non-radiative recombination ability, the emission intensity decays monotonically with increasing temperature. And the activation energy of luminescence intensity ( Ea ) can be calculated using the Arrhenius equation (I):

[0080]

[0081] Among them I PL and I0 represent the emission intensity at a single temperature (T) and 0K, respectively, while k B is the Boltzmann constant. Figure 8 k shows that the activation energy is 44.42 eV, which is greater than the thermal dissociation energy of free excitons at 300 K (~26 meV). The reason for the large activation energy is due to the strong electron-quantum confinement in the zero-dimensional hybrid halide structure, which promotes the formation of self-trapped excitons and overcomes thermal decomposition, ultimately achieving efficient self-trapped exciton-induced broadband light emission. As the temperature increases from 80 K to 300 K, the deformable lattice produces a significant electron-phonon coupling effect, resulting in a gradual widening of the half-peak width of the emission spectrum. In order to evaluate the deformability of the zero-dimensional structure and the strength of the electron-phonon coupling, we calculated the Huang-Ries coefficient (S) according to the following formula (II).

[0082]

[0083] in ћ ωphoton represents the phonon frequency (e.g. Figure 8 k). The Huang-Kun factor obtained by fitting is 52, which is larger than that of traditional semiconductor materials such as ZnSe (0.3) and CdSe (1.0). In addition, the phonon frequency (17.25 meV) corresponds to the [In / SbCl6] 3- The strong peak of the octahedral stretching vibration mode (153 cm -1 ) is a good match (such as Fig.15 The large Huang-Kun factor and the stretching vibrations in the anionic octahedron further demonstrate the strong electron-phonon coupling in the zero-dimensional hybrid structure.

[0084] At the same time, in order to increase [DADPA]In 0.73 Sb 0.17 The universality of Cl6·H2O, the present invention has carried out relevant tests on its environmental stability. Fig.16 As shown, when [DADPA]In 0.73 Sb 0.17 After the Cl6·H2O crystals were exposed to humid air for one month, the powder diffraction peaks still matched the simulated diffraction peaks, and the luminescence intensity was close to the original value, indicating that the structure and luminescence were extremely stable. 3+ In order to overcome the low color rendering index of commercial white light emitting diodes, the present invention utilizes [DADPA]In 0.73 Sb 0.17 The advantages of high photon quantum yield and wide half-peak width of Cl6·H2O were further explored for its potential application in solid-state white light-emitting diodes. 0.73 Sb 0.17 Cl6·H2O (yellow phosphor) and commercially available BaMgAl 10 O 17 :Eu 2+ A mixture of blue phosphor and UV light is coated on a UV chip to create a light bulb. Fig.17 As shown in Figs. a and 17b, the lamp emits bright white light when driven by a current of 20 mA. The electroluminescent spectrum contains a double emission peak of a narrow peak (70 nm) and a broad peak (128 nm), the CIE coordinates are (0.34, 0.32), and the correlated color temperature is 4895 K. As is well known, the color rendering index is a key indicator that reflects the ability of a white light source to display accurate colors compared to sunlight. It is worth noting that the color rendering index (93.1) of the light-emitting diode manufactured by the present invention is greater than that of traditional fluorescent light sources (65) and YAG:Ce-based 3+ In order to monitor whether there is a reabsorption effect between two corresponding phosphors, the present invention measures the corresponding electroluminescence spectra under different working currents (such as Fig.17 c). When the current increases from 20mA to 120mA, the spectral intensity of the dual emission peaks increases independently, and there is no energy interaction between the two phosphors, and the CIE coordinates, color temperature and color rendering index are almost unchanged, which indicates that the self-absorption between the phosphors is negligible and that [DADPA]In 0.73 Sb 0.17 Cl6·H2O has potential applications in high-power white light LEDs.

[0085] Next, the soft lattice and various zero-dimensional crystal structures inspired the present invention to further explore whether it can produce fluorescence conversion under the stimulation of small chemical molecules. Here, the present invention prepared high-quality [DADPA]In by microwave irradiation-assisted mechanical exfoliation 0.73 Sb 0.17 Cl6·H2O nanocrystals (NCs), the specific operation is as follows.

[0086] Example 4 [DADPA]In 0.83 Sb 0.17 Preparation of Cl6∙H2O nanoparticles

[0087] 1) Using an agate mortar and pestle, the [DADPA]In obtained in Example 3 0.83 Sb 0.17 Cl6∙H2O crystals were ground for 2 h;

[0088] 2) The obtained powder was dispersed in ethanol solvent, and then the suspension was placed in a microwave digestion oven and heated in a 500 W microwave oven for 17 h;

[0089] 3) Isolation of [DADPA]In by centrifugation 0.83 Sb 0.17 Suspension of Cl6∙H2O to obtain microparticles;

[0090] 4) The obtained microparticles were washed with ethanol and dried in a vacuum dryer at 80°C for 10 h to obtain [DADPA]In 0.83 Sb 0.17 Cl6∙H2O nanoparticles.

[0091] It is worth noting that Fig.19 As shown, the well-dispersed nanorods in ethanol showed the same bright yellow emission under UV excitation. 0.73 Sb 0.17 The sensing performance of Cl6·H2O nanoparticles was investigated. The present invention monitored the photoluminescence spectra before and after adding various organic solvents to monodisperse colloidal nanorods. Then, 100 μ Aromatic hydrocarbon derivatives of L include benzene (C6H6), dimethylbenzene (C6H5(CH3)2), ethylbenzene (C6H5C2H5), vinylbenzene (C6H5CHCH2), methoxybenzene (C6H5OCH3), fluorobenzene (C6H5F), chlorobenzene (C6H5Cl), bromobenzene (C6H5Br), iodobenzene (C6H5I), and nitrobenzene (C6H5NO2) as sensing targets. Fig.18 As shown in a, the luminescence of colloidal NCs under UV light is completely quenched by nitrobenzene, while colloidal NCs interfered by other organic solvents still show bright yellow light emission. Fig.18The synchronous luminescence spectra of b and 18c show that the emission intensity of nitrobenzene drops to 0.72%, while the emission intensity in other solvents remains almost unchanged. In order to carefully study the luminescence quenching performance, the present invention further utilizes a series of organic solvents containing various functional groups, such as alcohol, acetone, acetonitrile, acetylacetone, hydroquinone, cyclohexane, hexane, tetrahydrofuran, dichloromethane and bromoform as external chemical interferences. Fig. 20 As shown, in organic solvents (100 μ After soaking in L for more than 25 hours, all the luminescence intensities were almost close to the original data of the sample, indicating that it did not have fluorescence quenching phenomenon to other organic solvents. Subsequently, considering the importance of fluorescence contrast and the selectivity of fluorescent probe detection, the present invention mixed other aromatic hydrocarbon derivatives with a trace amount of nitrobenzene (volume ratio of 1%) to form a mixed solvent for anti-interference experiments, the purpose of which was to explore the effect of [DADPA]In 0.73 Sb 0.17 The detection selectivity of Cl6·H2O NCs for nitrobenzene. Fig.21 As shown, [DADPA]In 0.73 Sb 0.17 The fluorescence of Cl6·H2ONCs is still quenched by a small amount of nitrobenzene in the mixed solvent, but is almost unaffected by other organic solvents, showing an ultra-high selectivity for nitrobenzene.

[0092] like Fig. 22 As shown, after organic solvent immersion, all [DADPA]In 0.73 Sb 0.17 The diffraction peaks of Cl6·H2O NCs powder are consistent with the simulation data, indicating that its structure is highly stable. More importantly, [DADPA]In 0.73 Sb 0.17 The fluorescence of Cl6·H2O NCs can be restored after washing with benzene, and the reactivated fluorescence intensity is almost the same as the original value, indicating that the luminescence has a reversible effect on nitrobenzene (e.g. Fig.18 d). To confirm the repeatability of the reversible quenching-recovery process, the present invention monitored [DADPA]In during the continuous immersion-cleaning process. 0.73 Sb 0.17 Different emission intensities of Cl6·H2O NCs. Fig.18 As shown in Figure d, even after 20 consecutive cycles, the decay of its emission intensity is negligible, and the colloidal NCs photo shows a repeatable quenching-recovery cycle, which indicates that it has good luminescence reversibility and repeatability. Considering that the detection limit is also another key indicator of sensing, the present invention has been carried out at a concentration of 1×10 -2 Up to 1×10 -7Fluorescence titration experiments were carried out in a C6H5NO2 / C6H6 dilute solution. Fig.18 As shown in e, when the concentration of C6H5NO2 / C6H6 solution is reduced to 1×10 -6 (1ppm), the fluorescence can be quenched. Fig.18 f, at 1×10 -8 -10 -7 More detailed emission spectra of ultra-dilute C6H5NO2 / C6H6 solutions show that the detection limit can be reduced to 4×10 -7 (0.4ppm). Fig.18 As shown in g, the emission intensity decreases monotonically with the increase of C6H5NO2 concentration, and the quenching effect (I0 / I-1) is linearly related to the concentration (R 2 =0.99987), indicating that the detection effect is excellent. The above results show that [DADPA]In 0.73 Sb 0.17 Cl6·H2O NCs can be used as an excellent fluorescent probe with high selectivity, sensitivity and reproducibility to detect nitrobenzene.

[0093] At present, considering the high photon quantum yield and large Stokes shift of zero-dimensional metal halides, these halides have been explored as efficient X-ray scintillators, so the present invention further explored the scintillation performance of the [DADPA]InX6·H2O family. Taking the commercially available cerium-doped aluminum garnet (Ce:LuAG) as the standard reference, the radiation luminescence characteristics of the [DADPA]InX6·H2O series were studied. First, based on the photon cross-section database, the X-ray absorption spectra of [DADPA]InX6·H2O and Ce:LuAG were plotted in a wide range of photon energy (100~103keV). Due to the lower atomic number (Zeff) component, the X-ray attenuation efficiency of the [DADPA]InX6·H2O family is slightly inferior to that of Ce:LuAG (such as Fig.23 Under 30keV X-ray excitation, the [DADPA]InX6·H2O series exhibited the same broadband light emission as under UV excitation, demonstrating the same radiative recombination mechanism that has been proposed in many previous reports (e.g. Fig.24 a). Although the original [DADPA]InX6·H2O has poor scintillation performance, the Sb 3+ Doping, [DADPA]In 0.73 Sb 0.17Cl6·H2O has an ultra-high light quantum yield and its radiation luminescence intensity is also significantly better than commercial Ce:LuAG. By integrating the peak area of ​​their radiation spectra, its light yield was determined to be 2.1 times that of Ce:LuAG. Based on the light yield of Ce:LuAG (25,000 photons / MeV), its light yield was evaluated to be 51875 photons / MeV, which has exceeded three-dimensional CsPbX3 (about 21000 photons / MeV), (PPN)2SbCl5 (49000 photons / MeV) and most traditional inorganic scintillators such as CdWO4 (28000 photons / MeV), NaI: Tl (45000 photons / MeV), CsI:Na (41000 photons / MeV), LYSO (33200 photons / MeV), etc. Fig.24 b). This excellent scintillation performance is due to sufficient X-ray attenuation, ultra-high light quantum yield and negligible self-absorption. It is worth noting that [DADPA]In 0.73 Sb 0.17 Cl6·H2O is the first indium-based halide scintillator with high light yield, which opens a new application window in this field. Fig.24 c, [DADPA]In 0.73 Sb 0.17 Cl6·H2O single crystal at 4001.4-47625.2 μ Gyair / s range, the radiation luminescence intensity obtained by being excited by X-rays of different dose rates also increases monotonically with the increase of dose rate. Fig.24 As shown in d, the linear fitting of the X-ray dose rate dependence of the radiation intensity gives an ultra-low detection limit of 98.3 nGyair / s, which is lower than LYSO (3.5 µ Gyair / s), CdZnTe (5 µ Gyair / s) and 5.5 for normal medical diagnosis μ The dose rate of Gyair / s is much lower. In addition, the radiation stability of X-rays is another key indicator for X-ray scintillators and radiographic applications. Fig.24 As shown in e, under continuous X-ray irradiation at a dose rate of 27 mGyair / s, [DADPA]In 0.73 Sb 0.17 The emission intensity of the radioluminescence of Cl6·H2O remained stable within 40 h, which indicates that it has extremely high radioluminescence stability and strong tolerance to X-rays.

[0094] In view of its high light yield, ultra-low detection limit and strong radiation stability, the present invention uses [DADPA]In 0.73 Sb 0.17Cl6·H2O is used as an example to further explore its related applications in X-ray imaging. First, based on X-ray imaging, the present invention prepares a scintillating screen as a display component on the X-ray imaging optical system, and selects a series of small electronic devices as target objects (such as Fig.25 a). Next, the present invention uses an electronic box containing a metal wire as the first detection object. The metal wire inside is invisible to the naked eye under the sun. However, under the irradiation of X-rays, the insulating shell and the metal wire have different absorption capabilities for X-rays, resulting in a strong contrast in the intensity of the residual X-ray radiation. After conversion through the scintillation screen, an optical image is formed. Finally, a digital camera is used to clearly record the imaging photos inside the metal wire (such as Fig.25 b). Similarly, under X-ray irradiation, the metal wire encapsulated in the fuse tube can also be clearly observed. In order to further evaluate the spatial resolution of X-ray imaging, the present invention uses the oblique edge method to perform modulation transfer function (MTF) on the image. Fig.25 As shown in c-25d, when MTF is equal to 0.2, the spatial resolution of the scintillator screen is extracted as 25.15 lp / mm, which is much better than metal halide scintillators such as CsPbBr3:Lu (16.8 lp / mm), BA2PbBr4:Mn (10.7 lp / mm), Rb2AgBr3 (10.2 p / mm), and CsCu2I3 (7.5lp / mm). At the same time, afterglow can also be used as another important indicator of scintillator, because long-term radiation afterglow can seriously cause ghosting of imaging or affect the lag after X-ray cutoff. The present invention uses [DADPA]In 0.73 Sb 0.17 As an example, the afterglow intensity of Cl6·H2O after X-ray segmentation was measured. Fig.25 As shown in e, the afterglow signal disappears quickly within 2.75 ms after the X-ray source stops, reflecting the high contrast of its imaging. In short, the high spatial resolution and negligible afterglow lifetime prove that [DADPA]In 0.73 Sb 0.17 Cl6·H2O scintillator has excellent X-ray imaging performance.

[0095] Comparative Example 1

[0096] The difference from Example 3 is that the reaction temperature in step 2) is 150°C.

[0097] The compound prepared in Comparative Example 1 was determined to have a Sb doping concentration of 10% by inductively coupled plasma optical emission spectroscopy (as shown in Table 2), so the molecular formula of the prepared compound is [DPDPA]In 0.90 Sb 0.10 Cl6∙H2O.

[0098] Table 2

[0099]

[0100] like Fig.26 As shown, the powder diffraction pattern of the compound prepared in Comparative Example 1 is consistent with the data of the single crystal structure simulation, indicating that the purity of the compound prepared in Comparative Example 1 is close to the theoretical value (100%). Fig. 27 As shown, the compound prepared in Comparative Example 1 has narrow excitation and emission spectra, with main peaks at 270 and 568 nm, respectively, a half-peak width of 125 nm and a Stokes shift of 278 nm. Fig.28 As shown, the quantum yield of the compound prepared in Comparative Example 1 is 35.65%, which is much lower than that in Example 3. It can be seen from Example 3 and Comparative Example 1 that when the reaction temperature is too high, the doping concentration of the Sb element will be affected, causing the molecular formula of the prepared compound to change, thereby affecting the performance of the compound.

[0101] Comparative Example 2

[0102] The difference from Example 3 is that in step 1), the organic solvent is N,N-dimethylformamide.

[0103] The compound prepared in Comparative Example 2 has a doping concentration of Sb element of 7% as determined by inductively coupled plasma optical emission spectroscopy (as shown in Table 3), so the molecular formula of the prepared compound is [DPDPA]In 0.93 Sb 0.07 Cl6∙H2O.

[0104] Table 3

[0105]

[0106] like Fig.29 As shown, the powder diffraction pattern of the compound prepared in Comparative Example 2 is consistent with the data of the single crystal structure simulation, indicating that the purity of the compound prepared in Comparative Example 2 is close to the theoretical value (100%). Fig.30 As shown, the compound prepared in Comparative Example 2 has narrow excitation and emission spectra, with main peaks at 361 nm and 610 nm, respectively, and a half-peak width of 150 nm and a Stokes shift of 249 nm. Fig.31 As shown, the quantum yield of the compound prepared in Comparative Example 2 is 34.75%, which is much lower than that in Example 3. It can be seen from Example 3 and Comparative Example 2 that the type of organic solvent added during the reaction will also affect the Sb-doped [DADPA]In 0.83 Sb 0.17 Preparation and properties of Cl6∙H2O.

[0107] In summary, the present invention synthesizes a new type of hybrid lead-free halide [DADPA]In by a simple solution method. 0.73 Sb 0.17 Cl6·H2O is used as an environmentally friendly luminophore, and its quantum yield is close to 100%. Systematic experimental and theoretical studies have shown that the synergistic effect of strong quantum confinement and rational chemical doping can promote the generation of high emission efficiency, which provides a new synthetic strategy for exploring highly ideal halide luminophores. At the same time, [DADPA]In 0.73 Sb 0.17 The broadband light emission exhibited by Cl6·H2O not only enables its advanced application in white light LEDs, but also can be used as a fluorescent probe of nitrobenzene with high selectivity, sensitivity and reproducibility. Importantly, the high light quantum yield, negligible self-absorption and strong X-ray absorption ability enable it to exhibit superior X-ray scintillation performance. This is the first report on indium halide-based X-ray scintillators, opening up new application windows in the fields of X-ray imaging, medical diagnosis and radiation monitoring. This work highlights the multiple advantages of zero-dimensional mixed indium halides, such as non-toxicity, stability and excellent luminescence properties, which will promote its cutting-edge applications in the field of optoelectronics.

[0108] Although the present invention has been described in detail by referring to the accompanying drawings and in combination with the preferred embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, a person of ordinary skill in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions shall be within the scope of the present invention. Any person skilled in the art who is familiar with the present technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, and all of these shall be within the scope of protection of the present invention. Therefore, the scope of protection of the present invention shall be subject to the scope of protection of the claims.

Claims

1. A zero-dimensional hybrid indium-based halide material, characterized in that: The molecular formula of the zero-dimensional hybrid indium-based halide material is [DADPA]In 0.83 Sb 0.17 Cl6·H2O, wherein DADPA is 3,3'-diaminodipropylamine.

2. The method for preparing the zero-dimensional hybrid indium-based halide material according to claim 1, characterized in that: InCl3, SbCl3 and 3,3'-diaminodipropylamine are added to the mixed solution, and the mixture is heated and stirred continuously to dissolve; the obtained solution is transferred and sealed in a reaction container, and then heated at 60-85°C for at least 5 days, and cooled to room temperature to obtain the product.

3. The method for preparing the zero-dimensional hybrid indium-based halide material according to claim 2, characterized in that: The molar ratio of InCl3, SbCl3 and 3,3'-diaminodipropylamine is (1-2): (1-2):

1.

4. The use of the zero-dimensional hybrid indium-based halide material according to claim 1, characterized in that: The zero-dimensional hybrid indium-based halide material is applied to the fields of white light emitting diodes and fluorescent probes.

Citation Information

Patent Citations

  • Organic-inorganic hybrid metal halide perovskite compound, preparation method and application

    CN114716324A

  • Metal halide perovskites, methods, and devices

    US9896462B1